Comparing the Smoking Status of Working Adolescents with Adolescents Enrolled in High School in Turkey - KARADAĞ, BÜLENT TANER (MARY ANN LIEBERT INC, 2013)
Smoking is one of the most important public health problems. There is limited data about the smoking status of working adolescents. In this study we aimed to compare the smoking status of working adolescents with adolescents enrolled in high school in Turkey. Workers were recruited from a vocational training center, and control subjects were from a local high school. Questionnaires about socioeconomic status and smoking were applied. Eight hundred and two participants (436 workers) were included in the study. The mean age of the participants was 16.8 years. Smoking frequencies were 40% and 21% for the workers' group and the control group, respectively (P < 0.001). Adolescent workers were more frequently exposed to second-hand smoke at home. Working [odds ratio (OR): 2.49, 95% confidence interval (CI): 1.81-3.43], age over 17 (OR: 1.77, 95% CI: 1.28-2.44), and male sex (OR: 1.57, 95% CI: 1.00-2.44) were found to be significantly effective on smoking in the logistic regression analysis. Working adolescents had significantly higher smoking rates and exposed to second-hand smoke at home than high school students. Further studies are needed to explore the reasons of higher smoking rates in working adolescents than in high school students.
Keywords: INTERVENTION; STUDENTS; YOUTH